2006
DOI: 10.1093/bioinformatics/btl064
|View full text |Cite
|
Sign up to set email alerts
|

Matched-pairs tests of homogeneity with applications to homologous nucleotide sequences

Abstract: Programs written in R to do the tests on nucleotides are available from http://www.maths.usyd.edu.au/u/johnr/testsym/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 20 publications
1
101
0
Order By: Relevance
“…The resulting alignment contained 6913 sites from the 26 species. We then applied the matched-pairs test of symmetry [38] to the data to determine whether the sequences were consistent with evolution under globally SRH conditions. The PP -plot in Figure 7 clearly shows that the data are consistent with evolution under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting alignment contained 6913 sites from the 26 species. We then applied the matched-pairs test of symmetry [38] to the data to determine whether the sequences were consistent with evolution under globally SRH conditions. The PP -plot in Figure 7 clearly shows that the data are consistent with evolution under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Following that each pair of observed and expected F matrices may be tested as in Waddell et al (2004), and the results summed. Finally, it is straightforward to extend the testing procedures of Waddell et al (2004) to include the relationship noted by Ababneh et al (2006). That is, the internal symmetry statistic of F, X 2* [F], equals X 2 [F] -GLS [F].…”
Section: Discussionmentioning
confidence: 99%
“…The data matrices are available from the corresponding author. Kim et al (1994) a Inferred from ITS1 sequence analysis (Yang et al 2010) b Named previously on the basis of zymodeme analysis (Xu et al 1984) c Identified as L. donovani according to the zymodeme, LON41, whereas recent analysis have shown that it is L. infantum (Ibrahim and Barker 2001) Compositional heterogeneity was evaluated using Chisquare (# 2 ) tests implemented in PAUP* 4.0b10 (Swofford 2002) and assessed using the software SeqVis v.1.5 (Ho et al 2006) to visualize and to conduct matched-pairs test of symmetry (Ababneh et al 2006). Evidence of evolution under conditions more complex than that assumed by commonly applied models (i.e., stationary, reversible, and homogeneous conditions) was inferred if the scatter of dots in the tetrahedral plots was widely dispersed and if x% of the matched-pairs test of symmetry produced p values greater than or equal to x; this procedure is consistent with that advocated by Jermiin et al (2008).…”
Section: Sequence Alignment and Analysesmentioning
confidence: 99%